Definition and Types of Time Management Obstacles for Nursing - Qtait, Mohammad; Alarab, Seyyan (International Journal of Innovative Research in Medical Science, 2018)
Aim: This paper critically examines the research literature relating to the obstacles time management and definition of time management. Background: Time management is a skill and behaviors that become a aspect of one’s individual and professional life, it is the key to increase the productivity of nursing, but also helps to copy tension more efficiently. During the last years, there has been growing recognition of the status of time in today’s global and fast growing society, and increasing in technology. Method: This review contain 27 empirical studies and book on time management conducted between 2000 and 2018, by research in google. Findings: thorough search for the existing literature revealed a lack of study related to obstacles of time management, and discuss the concept obstacles of time management in nursing work and concern the obstacles of time management techniques. This review offers an overview of research on time management and obstacles of time management. The reviewed research displays many limitations as. First, time management has been defined and operationalized in a different of ways. Some instruments were not trustworthy or valid, which could account for unstable findings. Second, very little attention was given to nursing and health field. There is a need for more accurate research into the obstacles of time management in nursing and health professional. Conclusion: Review of article for obstacles time management, time management important for nurses, and effect on performance. Little study in obstacles of time management for nurses, study appear type of time management obstacles personal, administration and organizational obstacles, method of measurement of obstacles by experiment and questionnaire